Trade-offs and synergies of climate change adaptation strategies among smallholder farmers in sub-Saharan Africa: A systematic review - Akinyi, Devinia Princess; Karanja Ng'ang'a, Stanley; Girvetz, Evan Hartunian (Elsevier, 2021)
Climate change adaptation strategies provide a cushion for smallholder farmers, especially in sub Saharan Africa against the risks posed by climate hazards such as droughts and floods. However, the decision-making process in climate adaptation is complex. To better understand the dynamics of the process, we strive to answer this question: what are the potential trade-offs and synergies related to decision-making and implementation of climate adaptation strategies among small holder farmers in sub-Saharan Africa region? A systematic literature review methodology was used through the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) statement with the four-stage inclusion/exclusion criteria to identify the literature from selected databases (Scopus and Google Scholar). The climate adaptation strategies are organized into five broad categories (crop management, risk management, soil/land management, water manage ment, and livestock management strategies). Evidence suggests that potential trade-offs may arise concerning added costs, additional labor requirements, and competition among objectives or available resources. The synergies, on the other hand, arise from implementing two or more adaptation strategies concurrently in respect of increased productivity, resilience, yield stability, sustainability, and environmental protection. Trade-offs and synergies may also differ among the various adaptation strategies with minimum/zero tillage, comparatively, presenting more trade offs. The development and promotion of low-cost adaptation strategies and complementary climate adaptation options that minimize the trade-offs and maximize the synergies are suggested. Skills and knowledge on proper implementation of climate change adaptation strategies are encouraged, especially at the local farm level.